RISK MANAGEMENT ANALYSIS IN RURAL BANKS (BPR) MERGER (CASE STUDY: 6 BPRs THAT ARE IN THE PROCESS OF MERGING INTO ONE IN MALANG RAYA) - Nilam Yunida; P. Basuki Hadiprajitno (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This case study research aims to determine the risks that will increase during the BPR merger process based on the risk rating. The research was conducted on 6 (six) BPRs in the Greater Malang area which were in the process of being merged on December 31, 2022. This research was conducted in 4 (four) stages, which included assessing and determining the risk rating of 6 (six) BPRs individually, financial consolidation, assessing and determining the estimated risk rating of BPRs after the merger and the last was preparing recommendations for downgrading risk and risk mitigation. The results of this study indicate thatPost-merger credit risk and operational risk ratings of BPRs are projected to increase. This was mainly due to the low quality of productive assets originating from the six BPRs individually prior to the merger, inadequate BPR IT systems and an unstructured BPR office network that was deemed inefficient.